Provocation by Challenges: Optimizing Experience of Addressing Mathematical Tasks With High Cognitive Demand - Baldeón-de la Cruz, Maruja Dionisia (2020)
High cognitive demand mathematical tasks involve exercising skills to analyze, infer, relate and reflect on arithmetic, geometric and statistical information. In its development, student engagement is crucial to overcome increasingly complex situations in the learning process of the Peruvian school system. These variables are of vital importance because students need to avoid negative influences that cause academic failure or dropout, so it is valuable to live experiences of motivational improvement of their mathematical behavior to achieve permanent success in this area. In this proposal, the objective was to check whether the effects of a challenge provocation experience, based on Flow’s theory, optimized the approach to mathematical tasks with a certain cognitive demand. The design was of a pre-experimental quantitative type. A sample of 76 students was included. The instrument was the test of arithmetic problems with multiple cognitive demand. The results allowed concluding that the program stimulated the solution of memory tasks and problems with non-connective information, but its effect was less and slower in addressing tasks with high cognitive demand. The study contributed to verifying the benefits of scaffolding based on flow strategies, according to the challenges that stimulate the cognitive independence of the student who learns to tackle cognitive tasks, in accordance with the expertise and commitment obtained through interaction with the teacher or mediator.